Soybean - as a source of valuable food. (Texas Journal of Multidisciplinary Studies, 2022)
An alternative to meat, a cheap source of high-quality protein in the face of rising prices for livestock products in the world market, soybeans have been studied in Surkhandarya region, and the analysis has identified promising areas for food security in the region.